Open, closed or a bit of both: a systematic review and meta-analysis of staged thoraco-abdominal aortic aneurysm repair - Muston, Benjamin T.; Bilbrough, James; Bushati, Ymer; Wilson-Smith, Ashley R.; Misfeld, Martin; Yan, Tristan (Annals of Cardiothoracic Surgery, 2023)
Background: Staged procedures are one strategy found to be beneficial for medium- to high-risk Crawford extent I–III thoraco-abdominal aortic aneurysm (TAAA) repair patients and may be performed through a variety of techniques. This review sought to compare the primary outcomes of spinal cord ischemia (SCI) and long-term mortality between three cohorts grouped by approach: open, endovascular, and hybrid. Methods: In accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a total of 919 references were extracted from a search of three online databases (Embase, PubMed, Scopus). Following application of inclusion/exclusion criteria and data extraction, quantitative meta-analysis was undertaken utilizing a random effects model. Kaplan-Meier (KM) curves were digitized and aggregated to graph estimated survival. Results: A total of 20 studies representing 924 patients were included. SCI was highest in the endovascular group, at 9.8% of weighted means, followed by hybrid, and open groups at 3.2% and 1.4%, respectively. However, 30-day mortality was highest in the open group at 6.0%, followed by the hybrid group at 3.8%, and endovascular at 3.6%. Aggregated long-term survival estimations are shown graphically, extending to 5 years for open and endovascular cohorts, and 3 years for the smaller hybrid cohort. Conclusions: While all cases incorporated spinal drainage, monitoring and staging for spinal protection, there is innate difference in approach when examining for cord ischemia. This systematic review and meta-analysis of staged TAAA repair describes the first comparison between cohorts of open and endovascular approach, revealing the increased risk of SCI and long-term mortality in endovascular repair.